Analisis tingkat kontribusi teknologi pada produksi gula di pabrik gula Gempolkrep Mojokerto: Analysis of technology contribution rate to sugar production in Gempolkrep Mojokerto sugar factory - Yulianto, Teguh; Yuliati, Nuriah; Syah, Mirza Andrian (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2025)
The sugar industry in Indonesia plays an important role in supporting national food security. Sugar factories as one of the vital sectors not only produce sugar for domestic consumption but also contribute to the local economy and the agricultural sector, especially sugar cane. Gempolkrep Sugar Factory, which has been operating since 1849, is one of the sugar factories that faces challenges in terms of increasing production yields, as seen from the stagnation of yields around 8% in the last 6 years. This study aims to analyse the condition of the sugar production process, identify the contribution of technology to production, and determine the priority of improvements needed at Gempolkrep Sugar Factory. The research methods used are descriptive method to describe the production process, technometric method to assess technology contribution, and AHP (Analytical Hierarchy Process) method to determine improvement priorities. The results of this study show that the sugar production process at Gempolkrep Sugar Factory consists of 7 stages, with the technology applied classified as semi-modern with a TCC value of 0.675. The main improvement priority that must be done is machine modernisation with an AHP score of 0.473 which is focused on improving the IoT-based monitoring system with an AHP score of 0.460. The conclusion from these results is that implementing improvements based on existing priorities will help increase production yields and produce more consistent sugar products.